Orbitofrontal connectivity with resting-state networks is associated with midbrain dopamine D3 receptor availability. - Cole, D; Beckmann, C; Searle, G; Plisson, C; Tziortzi, A; Nichols, T; Gunn, R; Matthews, P; Rabiner, E; Beaver, J (2012)
Animal research and human postmortem evidence highlight the importance of brain dopamine D3 receptor (D3R) function in multiple neuropsychiatric disorders, including addiction. Separate anatomical and functional neuroimaging findings implicate disrupted frontal cortical connectivity with distributed brain networks in processes relevant for these diseases. This potential conjunction between molecular and functional markers has not, however, been tested directly. Here, we used a novel combination of [(11)C]-(+)-PHNO positron emission tomography and resting-state functional magnetic resonance imaging in the same healthy individuals to investigate whether differences in midbrain D3R availability are associated with functional interactions between large-scale networks and regions involved in reward processing and cognition. High midbrain D3R availability was associated with reduced functional connectivity between orbitofrontal cortex (OFC) and networks implicated in cognitive control and salience processing. The opposite pattern was observed in subcortical reward circuitry and the "default mode" network, which showed greater connectivity with OFC in individuals with high D3R availability. These findings demonstrate that differential interactions between OFC and networks implicated in cognitive control and reward are associated with midbrain D3R availability, consistent with the hypothesis that dopamine D3R signaling is an important molecular pathway underlying goal-directed behavior.